2013
DOI: 10.1111/jth.12297
|View full text |Cite
|
Sign up to set email alerts
|

Retinal vein and artery occlusions: a risk factor for stroke in atrial fibrillation

Abstract: Summary. Background: Retinal vascular occlusions may constitute an independent risk factor for stroke in patients with atrial fibrillation. Methods: We performed a retrospective study on a nationwide cohort with atrial fibrillation from 1997 to 2008. The rate of stroke/systemic thromboembolism (TE)/transitory ischemic attack (TIA) was determined for atrial fibrillation patients with and without a history of retinal vascular occlusion. A Cox regression analysis, adjusted for risk factors and medications, was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 35 publications
1
39
0
4
Order By: Relevance
“…The risk of stroke in RAO patients was significantly higher compared with RVO (Table 4). 4,5,10,13,15 This is perhaps consistent with expectations, based on their pathophysiological associations. The Danish study also found that in patients with established atrial fibrillation and coexisting RAO or RVO could accentuate the risk of incident stroke.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…The risk of stroke in RAO patients was significantly higher compared with RVO (Table 4). 4,5,10,13,15 This is perhaps consistent with expectations, based on their pathophysiological associations. The Danish study also found that in patients with established atrial fibrillation and coexisting RAO or RVO could accentuate the risk of incident stroke.…”
Section: Discussionsupporting
confidence: 76%
“…The Danish study also found that in patients with established atrial fibrillation and coexisting RAO or RVO could accentuate the risk of incident stroke. 13 As some of the increased risks associated with RVO were attributed to other adverse cardiovascular co-morbidities in these patients, it is more likely that RAO and RVO remain important independent predictors of future stroke in patients suffering from atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations